Optical Wireless Communication - Ke, Xizheng; Dong, Ke.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
The book gives a detailed description of optical wireless communication (OWC), including optical laser communication, visible light communication, ultraviolet communication, underwater optical communication and future communication technologies. To achieve an integration between theory and practice, the book avoids tedious mathematical deductions and includes theoretical materials as exercises. Most of the exercises are originated from published journal articles. These exercises will aid the readers in understanding the basic concept and methods and evaluating their knowledge acquisition in the field of OWC. The book is structured into Ten chapters that covers main aspects of OWC: - Optical wireless communication system - Coherent optical communication - Modulation, demodulation, and coding - Atmospheric channel, channel estimation, and channel equalization - White LED communication - Underwater laser communication - Ultraviolet communication - Acquisition, aiming, and tracking technology - Partially coherent optical transmission - Optical communication in the future The book is a suitable reference for undergraduate or postgraduate students majored in communication engineering, electronic information engineering or computer science, as well as the engineers and technicians in related fields.
Optical Wireless Communication System -- Coherent Optical Communication -- Modulation, Demodulation, and Coding -- Atmospheric Channel, Channel Estimation, and Channel Equalization -- White LED Communication -- Underwater Laser Communication -- Ultraviolet Communication -- Acquisition, Aiming, and Tracking Technology -- Partially Coherent Optical Transmission -- Optical Communication in the Future.
Keywords: Telecommunication; Wireless communication systems; Mobile communication systems; Lasers; Optical communications; Microwaves, RF Engineering and Optical Communications; Wireless and Mobile Communication; Laser; Optical Communications; Optical communications; Wireless communication systems